2017
DOI: 10.1177/1545968317697031
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Phase Synchrony Reflects Clinical Status After Stroke: An EEG Study

Abstract: The PSIs correlated with performance on the activities of daily living scale but not with scores on a pure motor impairment scale. These results suggest that large-scale phase synchrony represented by IH-PSIs provides a novel surrogate marker for clinical status after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 27 publications
7
42
0
Order By: Relevance
“…Functional connectivity in several different frequency bands were investigated, with connectivity in the alpha band providing the strongest association with anodal tDCS response. Previous studies have demonstrated the functional significance of alpha oscillations which have been associated with post stroke subacute clinical status, motor performance and functional recovery (Dubovik et al, ; Kawano et al, ; Westlake et al, ). Furthermore, studies have reported alpha oscillations are associated with attention, memory, motor learning and performance (Harris, Dux, Jones, & Mattingley, ; Jensen, Gelfand, Kounios, & Lisman, ; Mottaz et al, ; Pollok, Boysen, & Krause, ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional connectivity in several different frequency bands were investigated, with connectivity in the alpha band providing the strongest association with anodal tDCS response. Previous studies have demonstrated the functional significance of alpha oscillations which have been associated with post stroke subacute clinical status, motor performance and functional recovery (Dubovik et al, ; Kawano et al, ; Westlake et al, ). Furthermore, studies have reported alpha oscillations are associated with attention, memory, motor learning and performance (Harris, Dux, Jones, & Mattingley, ; Jensen, Gelfand, Kounios, & Lisman, ; Mottaz et al, ; Pollok, Boysen, & Krause, ).…”
Section: Discussionmentioning
confidence: 99%
“…This method provides evidence that attentional top-down control not only coordinates the sensory input to the cortex by thalamic gating, but also changes the cortical excitability and effective connectivity that mediates cortical gating between TR regions. The observation of perturbation effects caused by direct use of TMS-EEG will allow the characterization of excitability and effective connectivity changes according to the task at hand as well as changes due to diseases which impair networks such as stroke [61].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to directly modulate brain rhythms in a frequency and target-specific manner may provide insights into the functional roles of rhythmic activity. Moreover, this technique has clinical potential: modulation of impaired oscillations and synchrony may alleviate symptoms in patients with attention deficit hyperactivity disorder (Barry et al, 2003), Alzheimer's disease (Prichep et al, 2006), depression (Vuga et al, 2006), obsessive-compulsive disorder (Sherlin and Congedo, 2005), schizophrenia (Lee et al, 2006), and stroke (Kawano et al, 2017). each frequency (red line in panels A and C).…”
Section: Discussionmentioning
confidence: 99%